Telaah Manajemen Utang Luar Negeri Indonesia Dan Rekomendasi Kebijakan Dalam Perspektif Ekonomi Syariah - Purwanti, Neli; Dewi Anggini, Megah (Coopetition : Jurnal Ilmiah Manajemen, 2024)
This research examines Indonesia's foreign debt management from a sharia economic perspective, with the aim of providing policy recommendations that are in accordance with sharia principles. Foreign debt is an important instrument in financing development, but high levels of debt can give rise to various economic risks. Descriptive analysis is used to describe the current condition of Indonesia's foreign debt, including the amount, type and structure of debt. Meanwhile, qualitative analysis is used to evaluate existing debt management policies and their conformity with sharia economic principles and policy recommendations from a sharia economic perspective. The research results show that Indonesia's foreign debt continues to increase, with the composition dominated by long-term debt from various sources. From a sharia economic perspective, several current debt management policies are not fully in accordance with sharia principles, especially those related to the use of debt instruments that contain elements of usury. This research recommends several policy steps, including: increasing transparency and accountability in debt management, developing financing instruments that comply with sharia principles such as sukuk and waqf, and diversifying financing sources to reduce dependence on conventional foreign debt.